Cafe Online Ordering System for Triple E Cafe Enterprise using e-storefront model - Rosmaidi, Nur Hanis Nabihah (2025)
This paper proposes an e-storefront model to develop the Cafe Online Ordering System for Triple E Cafe Enterprise to help eliminate these inefficiencies of the existing manual ordering system. The system will try to smoothen the operational process by integrating e-commerce into it, which in turn will minimize waiting time, enhance customer experience, and have order accuracy. The system will provide facilities where customers can browse the menu, place orders, track orders, and make online payments securely. Staff can manage inventory, update order statuses, and handle customer feedback efficiently, while managers can manage sales reports without increasing the workload of the staff and minimizing human errors. Using the Adapted Waterfall Model for development, following a structured sequence of planning, analysis, design, implementation, testing, and documentation. the system will include user roles for managers, staff, and customers, ensuring a comprehensive functionality and usability aspect. The final system was evaluated through expert evaluation and usability testing involving 30 users. The results indicated high levels of user satisfaction in terms of functionality, interface design, and ease of use. Experts highlighted the system's effectiveness in supporting a smooth ordering process and recommended minor improvements. The implementation of the system led to significant improvements in the business process, including reduced human error, automated sales tracking, and better communication with customers. This study demonstrates the potential of adopting an e-storefront approach to modernize traditional cafe operations to improve customer engagement, and support business growth in a competitive digital environment.